PROBLEM OF AUTOMATIC CONTROL AND NUMERICAL MODELING OF THE SPEED OF OPTICAL FIBER EXTRACT IN THE PROCESS OF ITS MANUFACTURE - W. Wojcik; A.S. Tergeussizova (Academic Journal of Physical and Chemical Sciences, 2019)
This paper describes the basic design of the drum for pulling optical fiber. This is a key element that affects the speed and tension of the optical fiber, and ultimately its main geometrical parameters, such as the diameter and shape of the cross section, whose stability determines the performance characteristics of the finished optical fiber. Also, the work is devoted to the development of a mathematical model of the drum (coil), taking into account the dynamic equation of motion, inertia and speed changes. An open loop transfer function is obtained for a belt pulley, a motor and a speed controller with feedback control in proportion to an integral controller. A transient process was obtained through the channel “drawing speed - diameter” for various types of exhaust drums.